Graphene as a phase shifter element for reflectarray beam-steering at THz frequencies - Kamarudin, Muhammad Ramlee; Abbasi, Muhammad Inam; Qureshi, Suhail Asghar; Yamada, Yoshihide; Dahri, Muhammad Hashim; Zainal Abidin, Zuhairiah; Ramli, Nordin (The Electromagnetics Academy, 2025)
In Terahertz (THz) frequencies, using traditional phase delay components is extremely difficult, and graphene has the potential to be used in THz. Graphene is typically used at less than λ/16 dimensions. However, it can potentially change the properties of a unit cell in a reflectarray and act as an electronic phase-shifting element at λ/2 dimensions. Therefore, this paper proposes the design and application of graphene in unit cells to develop reflectarray beam steering. A metal-graphene hybrid structure is proposed in this work for designing the reconfigurable reflectarray antenna (RRA). The unit cell operating at 1.025 THz frequency consists of a thin graphene sheet as a phase-shifting element inside a golden ring, where graphene is used as the phase delay component. The variation in the chemical potential of graphene leads to changes in the reflection coefficient phase for each unit cell. A circular aperture array comprising a maximum of 489 elements shows a total of 80◦ beam-steering with side-lobe levels of less than −10 dB and a maximum gain of over 20 dBi. The −1 dB bandwidth of 12% was obtained at the centre frequency of 1025 GHz between 950 GHz and 1075 GHz. The aperture efficiency of the designed RRA is found to be 11%. This type of antenna could be an advent for the development of terahertz Reflecting Intelligent Surface (RIS).